1996
DOI: 10.1021/tx9600715
|View full text |Cite
|
Sign up to set email alerts
|

S-Methylation of O,O-Dialkyl Phosphorodithioic Acids:  O,O,S-Trimethyl Phosphorodithioate and Phosphorothiolate as Metabolites of Dimethoate in Mice

Abstract: O,O,S-Trimethyl phosphorodithioate and phosphorothiolate [(MeO)2P(S)SMe and (MeO)2P-(O)SMe, respectively are known from earlier studies to be impurities, delayed toxicants, and detoxication inhibitors in several major O,O-dimethyl phosphorodithioate insecticides. Our recent studies show extensive S-methylation of mono- and dithiocarbamic acids in mice, suggesting the possibility that phosphorodithioic acids such as (MeO)2P(S)SH might also undergo S-methylation. This possibility was examined in ip-treated mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Such enzymatic degradation behavior is observed in mouse 18) and human. 15,18) Since there is no other enzymatic metabolite, such as O,O -dimethyl phosphorodithioic acid or O,Odimethyl phosphorothioic acid, which are produced in mouse 19) and human, 20) CE is the only malathion-degradable enzyme in wheat kernels.…”
Section: Discussionmentioning
confidence: 99%
“…Such enzymatic degradation behavior is observed in mouse 18) and human. 15,18) Since there is no other enzymatic metabolite, such as O,O -dimethyl phosphorodithioic acid or O,Odimethyl phosphorothioic acid, which are produced in mouse 19) and human, 20) CE is the only malathion-degradable enzyme in wheat kernels.…”
Section: Discussionmentioning
confidence: 99%
“…2,8 Furthermore, the 31 P NMR chemical shifts for OP pesticides show upfield shifts when the OP is coordinated to transition metals. 3,4,8 Similarly, in studies of the series of compounds Ia-d containing different X substituents on the meta and para positions of the phenyl moiety, it was found that electron withdrawing substituents lead to an upfield shift of the 31 P signal, pointing to a shielding effect on the P atom. 9 However, contrary wise, in studies of the alkyl and aryl phosphinate ester series IIa-c Hoz, Buncel and co-workers 10b found that electron-withdrawing substituents (X) induced downfield shifts in 31 P chemical shift, i.e.…”
mentioning
confidence: 89%
“…2 To illustrate, interestingly, a literature survey showed that the 31 P NMR chemical shifts of structurally modified OP ester pesticides, replacing (RO)P=O by (RS)P =O, (RO)P=S and (RS)P=S functionalities, resulted in 31 P chemical shift changes by up to 100 ppm as summarized in Table 1. [3][4][5][6][7] In rationalizing such results one of the guiding principles that has come through theoretical and experimental studies is the concept of electronegativity, i.e. that increase in electron density of an atomic nucleus enhances its shielding, resulting in an upfield chemical shift.…”
mentioning
confidence: 99%
“…Mahajna et al [79] analyzed metabolism of O,O-dialkyl phosphorodithioate insecticides in mammals. Their study concerned with the possibility of S-methylation of phosphorodithioic acids such as (MeO) 2 P(S)SH, resulting in O,O,S-trimethyl compounds as metabolites.…”
Section: Biomonitoring Of Human Exposurementioning
confidence: 99%